Correlates of suicidal ideation in college women with eating disorders. Issue 6 (14th June 2018) - Goel, Neha J.; Sadeh‐Sharvit, Shiri; Flatt, Rachael E.; Trockel, Mickey; Balantekin, Katherine N.; Fitzsimmons‐Craft, Ellen E.; Monterubio, Grace E.; Firebaugh, Marie-Laure; Jacobi, Corinna; Wilfley, Denise E.; Taylor, C. Barr
Abstract: Objective: To identify the correlates of suicidal ideation (SI) in a large sample of college women with eating disorders (EDs). Method: A total of 690 female college students from 28 US colleges who screened positive for an ED, with the exception of anorexia nervosa, were assessed for SI. Univariate logistic regression analyses were performed to determine independent correlates of SI. Measures included: ED psychopathology, ED behaviors (i.e., binge eating, vomiting, laxatives, compulsive exercise), current co‐morbid psychopathology (i.e., depression, anxiety, insomnia), weight/shape concerns, ED‐related clinical impairment, and body mass index (BMI). All significant variables were included in a backward binary multivariate logistic regression model to determine which variables were most strongly associated with SI. Results: A total of 25.6% of the sample reported SI. All variables examined were significantly independently associated with SI, with the exception of compulsive exercise. Depression, anxiety, and vomiting remained as significant correlates of SI in the multivariate logistic regression model. Discussion: ED screening on college campuses should assess for suicidality, and prevention and treatment efforts should target vomiting and co‐morbid depression and anxiety symptoms to reduce risk of SI for high‐risk individuals.